Short Communication: Morphological variation of Coffea liberica from Batangas, Philippines with implications for sustainable coffee production and breeding programs - ABIGAIL MANGUIAT BALAN; PHEBE P. MENDOZA; ALAN RODELLE M. SALCEDO; GRECEBIO JONATHAN D. ALEJANDRO (Society for Indonesian Biodiversity, 2026)
Abstract. Balan AM, Mendoza PP, Salcedo ARM, Alejandro GJD. 2026. Short Communication: Morphological variation of Coffea liberica from Batangas, Philippines with implications for sustainable coffee production and breeding programs. Biodiversitas 26 (1): d270149. https://doi.org/10.13057/biodiv/d270149. Coffea liberica, locally known as